Practicing Psychologists Consulting Activities in the Structure of Specialist Training - Kulchytska, A. V. (Psychological Prospects Journal, 2011)
The article is devoted to the factors and mecha-nisms for efficient realization of consultative activities by psychologists. The concep-tual approaches for professional training of practicing psychologists are considered. The necessity of wider application of the data on individual approach and corrective work in the course of practicing psychologists training is underlined and grounded up.